Revision of the genus Typhlocybella Baker, 1903 (Hemiptera: Cicadellidae: Typhlocybinae: Dikraneurini) and description of a new species from Argentina. - Catalano, María Inés (2012)
The typhlocybine leafhopper genus Typhlocybella belonging to the tribe Dikraneurini was erected by Baker (1903) with T. minima from Nicaragua as the type species. DeLong and Knull (1946) added T. minuta from USA; Caldwell and Martorell (1952) added T. maculata from Puerto Rico, Ruppel & DeLong (1953) added T. parva from Mexico, and Catalano et al. (2009) added T. maidica from Argentina. Thus, five species of the genus have been reported previously, distributed throughout the Americas. In this paper, we review the previously described species included in the Typhlocybella, describe a new species, T. affinis n.sp. from Argentina, and re-describe the species T. parva. In addition, a key to identify Typhlocybella species is given.